P187 Estimating cost savings by introducing a reflex Hepatitis B virus screening algorithm in a sexual health service. (30th June 2016) - Bradshaw, Daniel; Muir, David; Rayment, Michael
Abstract : Background/introduction: BASHH recommends that screening for HBV infection may be with HBcAb, with reflex HBsAg testing in HBcAb-positive patients. False negative HBcAb (eg in acute HBV infection or with low assay sensitivity) is rare. At the time our laboratory did not routinely perform reflex HBsAg testing, placing the onus on clinicians, many of whom therefore requested both tests simultaneously (with redundant sAg tests being performed in the presence of a negative cAb). We wished to audit the extent of this practice and estimate cost savings by introducing reflex testing. Aim(s)/objectives: This was a retrospective case notes review of patients for whom HBcAb had been requested between 01/01/15 and 01/05/15. The cost of performing HBsAg testing was estimated at £3.60 per test. Methods: There were two hundred patients with HBcAb results: 110 (55%) male; median age 32 (IQR 26–39) years; 9 (4.5%) HIV-infected. Twenty-two (11%) tested HBcAb-positive of whom 5 (2.5%) were HBsAg-positive, 16 (8.0%) HBsAg-negative and 1 (0.5%) not tested for HBsAg. Of the HBcAb-positive individuals, requesting details were available for 10 cases: for 8/10 both HBsAg and HBcAb were requested initially. Of 178 (89.0%) HBcAb-negative individuals, HBsAg was performed for 49 (24.5%); all were HBsAg-negative. Across the Trust, 11, 500 HBcAb tests were requested in 12 months. Assuming 89.0% HBcAb-negativity, the cost of testing 24.5% of these patients for HBsAg would almost reach £10, 000. Results: Reducing HBsAg testing in HBcAb-negative individuals would provide savings. Reflex laboratory HBsAg should be implemented for HBcAb-positive patients.